Amorphization of Pseudocapacitive T−Nb2O5 Accelerates Lithium Diffusivity as Revealed Using Tunable Isomorphic Architectures. Issue 6 (9th March 2022) - van den Bergh, Wessel; Wechsler, Sean; Lokupitiya, Hasala Nadeesini; Jarocha, Lauren; Kim, Kwangnam; Chapman, James; Kweon, Kyoung E.; Wood, Brandon C.; Heald, Steve; Stefik, Morgan
Abstract: Intercalation pseudocapacitance can combine capacitor‐like power densities with battery‐like energy densities. Such surface‐limited behavior requires rapid diffusion where amorphization can increase solid‐state diffusivity. Here intercalation pseudocapacitive materials with tailored extents of amorphization in T‐Nb2 O5 are first reported. Amorphization was characterized with WAXS, XPS, XAFS, and EPR which suggested a peroxide‐rich (O2 2− ) surface that was consistent with DFT predictions. A series of tunable isomorphic architectures enabled comparisons while independently varying transport parameters. Through process of elimination, solid‐state lithium diffusion was identified as the dominant diffusive‐constraint dictating the maximum voltage sweep rate for surface‐limited kinetics ( v SLT ), termed the Surface‐Limited Threshold (SLT). The v SLT increased with amorphization however stable cycling required crystalline T‐Nb2 O5 . A current‐response model using series‐impedances well‐matched these observations. This perspective revealed that amorphization of T‐Nb2 O5 enhanced solid‐state diffusion by 12.2 % and increased surface‐limitations by 17.0 % (stable samples). This approach enabled retaining 95 % lithiation capacity at ∼800 mV s −1 (1, 600 C‐rate equivalent). Abstract : Faster lithium solid state diffusion : The maximum charge rates for T‐Nb2 O5 intercalation pseudocapacitance are limited by lithium solid state diffusion. Partial amorphization of T‐Nb2 O5 significantly enhanced this diffusion rate and enabled 95 % retention of lithiation capacity with fast voltage sweep rates up to ∼800 mV s −1 that is equivalent to a 1600 C‐rate.